La violencia de la historia entre relatos y testimonios: Argentina 1976 -83 - Oltramonti, Roberto (2019)
This study is to analyze the literature of the post-dictatorship period as a reconstruction of the trauma. The main topic is the investigation of the forms of writing that are used in the testimonial literature by writers such as Massimo Carlotto and Mario Villani. This genre entwines with various modes and techniques of writing. The texts that are studied are Le Irregolari: Buenos Aires Horror Tour written by Massimo Carlotto and Desaparecido: Memorias de un cautiverio written by Mario Villani and Fernando Reati.